2019
DOI: 10.21608/jfds.2019.36154
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Evaluation of Cookies Enriched with Different Blends of Spirulina platensis and Moringa oleifera Leaves Powder

Abstract: Cookies were produced from wheat flour with partial replacement with a combination of dried spirulina biomass and moringa leaves powder at different concentrations T1 (95:2:3), T2 (90:4:6) and T3 (85:6:9), respectively. 100% wheat flour cookies were used as the control sample. Quality characteristics of produced cookies were evaluated including the physical, chemical, sensory and antioxidant properties. The results showed significant differences in the physical properties of all cookie samples. Cookies with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Ogunsina et al, (2011) investigated producing cookies samples using wheat and debittered moringa seeds flour mixtures had high nutritive values especially in protein, iron and calcium. (Ashoush and Mahdy, 2019) found that, processed a type of bakery product such as cookies using dried moringa leaves had high nutritive values especially in protein, crude fibers and minerals. Thus, supplementation of wheat flour with moringa leaves and seeds powders could significantly raise the nutritional value of wheatmoringa composite flour, especially in micro-nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Ogunsina et al, (2011) investigated producing cookies samples using wheat and debittered moringa seeds flour mixtures had high nutritive values especially in protein, iron and calcium. (Ashoush and Mahdy, 2019) found that, processed a type of bakery product such as cookies using dried moringa leaves had high nutritive values especially in protein, crude fibers and minerals. Thus, supplementation of wheat flour with moringa leaves and seeds powders could significantly raise the nutritional value of wheatmoringa composite flour, especially in micro-nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…findings ofMahmoud (2017),Ashoush and Mahdy (2019) andRawung et al (2021). The results obtained in this study demonstrates that the incorporation of V. doniana in our diet could be beneficial to health with respect to free radical scavenging.…”
mentioning
confidence: 89%
“…Moreover, a trend has begun to add microalgae (cyanobacterial biomass) in fermented milk products to increase the functional product properties by promoting the viability of probiotics and also to improve their nutritional properties (Varga et al 2002;Beheshtipour et al 2013). Spirulina is frequently used for human consumption in various forms: tablets, capsules, or food additives such as dairy products (Varga et al 2002;Guldas and Irkın 2010;Malik et al 2013;Agustini et al 2016;Barkallah et al 2017;Darwish 2017;Szmejda et al 2018;Çelekli et al 2019;Narayana and Kale 2019;Çelekli et al 2020;Bosnea et al 2021), gelatin desserts (Gouveia et al 2008), and bakery products (De Marco et al 2014;Ashoush and Samar 2019;Grahl et al 2020;Da Silva et al 2021).…”
Section: Introductionmentioning
confidence: 99%